Cell-bound complement activation products associate with lupus severity in SLE. Issue 1 (5th May 2020) - Arriens, Cristina; Alexander, Roberta Vezza; Narain, Sonali; Saxena, Amit; Collins, Christopher E; Wallace, Daniel J; Massarotti, Elena; Conklin, John; Kalunian, Kenneth C; Putterman, Chaim; Ramsey-Goldman, Rosalind; Buyon, Jill P; et al.
Abstract : Objectives: To evaluate the association between lupus severity and cell-bound complement activation products (CB-CAPs) or low complement proteins C3 and C4. Methods: All subjects (n=495) fulfilled the American College of Rheumatology (ACR) classification criteria for SLE. Abnormal CB-CAPs (erythrocyte-bound C4d or B-lymphocyte-bound C4d levels >99th percentile of healthy) and complement proteins C3 and C4 were determined using flow cytometry and turbidimetry, respectively. Lupus severity was estimated using the Lupus Severity Index (LSI). Statistical analysis consisted of multivariable linear regression and groups comparisons. Results: Abnormal CB-CAPs were more prevalent than low complement values irrespective of LSI levels (62% vs 38%, respectively, p<0.0001). LSI was low (median 5.44, IQR: 4.77–6.93) in patients with no complement abnormality, intermediate in patients with abnormal CB-CAPs (median 6.09, IQR: 5.31–8.20) and high in the group presenting with both abnormal CB-CAPs and low C3 and/or C4 (median 7.85, IQR: 5.51–8.37). Odds of immunosuppressant use was higher in subjects with LSI ≥5.95 compared with subjects with LSI <5.95 (1.60 vs 0.53, p<0.0001 for both). Multivariable regression analysis revealed that higher LSI scores associated with abnormal CB-CAPs—but not low C3/C4—after adjusting for younger age, race and longer disease duration (p=0.0001), which were also independent predictors of disease severity (global R 2 =0.145). Conclusion: Abnormalities in complement activation as measured by CB-CAPs are associated with increased LSI.